The potential feasibility of mangrove crab (Scylla serrata) silvofishery aquaculture - HENDY RINALDY; JOHAN ISKANDAR; M. FANI CAHYANDITO; SUNARDI SUNARDI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rinaldy H, Iskandar J, Cahyandito MF, Sunardi. 2023. The potential feasibility of mangrove crab (Scylla serrata) silvofishery aquaculture. Biodiversitas 24: 3344-3354. The degradation of mangrove forests in Indonesia has reached more than 50%, and increases continuously. Sei Beduk is one of the Sub-districts in Batam City, Indonesia, that has mangrove forest damage where the density of trees per hectare is below the normal value of <1,000 trees per hectare. One approach that can be applied to overcome forest degradation is fisheries management with an ecosystem approach. This study aims to determine the suitable location for cultivating mangrove crab (Scylla serrata Forskål, 1775) and analyze the potential feasibility of S. serrata silvofishery cultivation using a quantitative approach with the Ecosystem Approach to Fisheries Management (EAFM) method. According to Slovin's calculations, a minimum of 100 people samples were obtained, and 147 samples were obtained at the time of data collection. The results showed that the location of the Perahu was highly potential for silvofishery S. serrata cultivation. The overall potential feasibility of silvofishery S. serrata cultivation in Sei Beduk, Batam was 53.10% or moderate/relatively good. The potential feasibility of S. serrata cultivation management planning is sufficient to support the sustainability of mangrove forests and allow it to be implemented. The feasible plan for managing S. serrata cultivation is to preserve ecology while improving and considering aquaculture policies and regulations. The relatively appropriate mangrove silvofishery cultivation in Sei Beduk, Batam, can provide community solutions to carry out silvofishery cultivation as a measure to overcome the problem of mangrove forest degradation, particularly in Sei Beduk, Batam.